The security of the FDH variant of Chaum's undeniable signature scheme - Ogata, Wakaha; Kurosawa, Kaoru; Heng, Swee Huay (IEEE, 2006)
In this paper, a new kind of adversarial goal called forge-and-impersonate in undeniable signature schemes is introduced. Note that forgeability does not necessarily imply impersonation ability. The security of the full-domain hash (FDH) variant of Chaum's undeniable signature scheme is then classified according to three dimensions, the goal of adversaries, the attacks, and the zero-knowledg (ZK) level of confirmation and disavowal protocols. Each security is then related to some well-known computational problem. In particular, the security of the FDH variant of Chaum's scheme with noninteractive zero-knowledge (NIZK) protocol confirmation and disavowal protocols is proven to be equivalent to the computational Diffie-Hellman (CDH) problem, as opposed to the gap Diffie-Hellman (GDH) problem as claimed by Okamoto and Pointcheval.